PENGARUH DIMENSI RELASIONAL DAN KOGNITIF MODAL SOSIAL TERHDAP KINERJA GURU DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL PADA SMK NEGERI DI KABUPATEN PATI - 11.52.02.0144, Makhali (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims at investigating of the relational dimension of social capital .and Cognitive Dimensions of Social Capital on Performance, Transformational leaderships moderated at SMK Negeri in Pati Regency. The specific aim is to investigate âHow isThe influence of Transformational leaderships can moderate the relational dimension of social capital and the cognitive dimensions of social capital to the teacherâs performanceâ. This study used a sample of teachers at SMK Negeri in Pati Regency, as many as 121 teachers . The sample was taken using randem sampling technique by proportional method 50 percent of the population. The analysis technique uses partial regression. The results of this study show that : (1) the relational dimension of social capital positive and significant to the teachers performance , (2) the cognitive dimensions of social capital positive and significant to the teacher performance , (3) transformational leadership and significant positive effect on teacher performance , (4) transformational leadership weaken the relationship between relational dimension of social capital to the teachers performance ,(5) transformational Leadership weakens the relationship between the cognitive dimension of social capital to the teachers performance. Keywords : relational dimension , cognitive dimension , transformational leadership , teacher performance .